Prognosis and Biological Function of miR-3195 in Non-Small Cell Lung Cancer [Retraction] - Lu Y; Zhang X; Zhang H; Zhu Z (Cancer Management and Research, 2023)
Lu Y, Zhang X, Zhang H, Zhu Z. Cancer Manag Res. 2022;14:169-176. We, the Editors and Publisher of Cancer Management and Research, have retracted the following article. Following publication of the article, concerns were raised about the duplication of images from Figure 4 with images from other unrelated articles. Specifically,